When does coopetition affect price unfairness perception? The roles of market structure and innovation - Sabri, Ouidade; Djedidi, Amina; Hani, Mouhoub (IDEAS Working Paper Series from RePEc, 2021)
Purpose This study aims to examine the critical role of types of coopetition (upstream/downstream), market structure (concentrated/competitive) and innovation (low vs high degree of innovation) that can affect the way consumers perceive the resulting price (un)fairness of new offerings. Design/methodology/approach Three between-subjects experiments involving different participant populations and product categories were conducted to test the research hypotheses. Findings The valence of the effect of types of coopetition (upstream/downstream) on price fairness is conditional on the market structure and the degree of innovation associated with the new product offering. Downstream (as opposed to upstream) coopetition is much more detrimental to perceptions of price fairness in a concentrated market than in a competitive and fragmented market. However, within a competitive market, downstream coopetition may lead to greater price fairness perception than upstream coopetition when the new product offering is highly innovative. Research limitations/implications The current study uses lab experiments with fictitious scenarios and focuses on two moderating variables: market structure and innovation perceptions. Future research may use field experiments and explore additional moderating variables that may annihilate the negative effect of downstream coopetition on price fairness perception, especially in a concentrated market. Practical implications In concentrated markets, firms should opt for upstream rather than downstream coopetition to limit the negative effect the announcement of coopetition has on price fairness evaluation. However, within a competitive market, when the new product offering resulting from coopetition is associated with a high perceived degree of innovation, firms should opt for downstream rather than upstream coopetition because of its positive impact on price fairness evaluation. Originality/value To the best of authors’ knowledge, this study is the first to demonstrate that new product development from coopetition has important implications for the perception of price fairness, leading to positive or negative effects depending on market structure and the degree of innovation of the new product offering. It then explores the conditions under which types of coopetition (upstream/downstream) might backfire.